2018
DOI: 10.1155/2018/9075318
|View full text |Cite
|
Sign up to set email alerts
|

The Antiosteoporosis Effects of Zhuanggu Guanjie Pill In Vitro and In Vivo

Abstract: We investigated the beneficial effects and underlying mechanisms of Zhuanggu Guanjie (ZGGJ) pill in osteoporosis in vitro and in vivo. Bone marrow macrophages from 4–6-week-old mice were cultured in the presence of macrophage colony-stimulating factor (15 ng/mL) and receptor activator of nuclear factor-κB ligand (30 ng/mL). Osteoclast differentiation was determined by quantification of tartrate-resistant acid phosphatase activity. Gelatin zymography was used to detect the activity of matrix metalloproteinases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Moreover, studies on animal models also proved that MMP-9 can be a marker for osteoclast activity [5]. Widely used ovariectomized rat model recently showed a significant decrease in MMP9 activity, observed by means of gelatin zymography, after pharmacological treatment [14]. Finally, human studies confirmed the overexpression of MMP-9 in subjects suffering from osteoporosis [26].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, studies on animal models also proved that MMP-9 can be a marker for osteoclast activity [5]. Widely used ovariectomized rat model recently showed a significant decrease in MMP9 activity, observed by means of gelatin zymography, after pharmacological treatment [14]. Finally, human studies confirmed the overexpression of MMP-9 in subjects suffering from osteoporosis [26].…”
Section: Discussionmentioning
confidence: 92%
“…e closer mechanism of these protective possibilities has to be clarified. e serum MMP-9 concentration was observed to be negatively correlated with BMD (bone mineral density) and is considered as a biochemical marker of bone resorption and remodeling [13,14] and an important marker in the early diagnosis of osteoporosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteinase 9 is a Zn 2+ -dependent proteolytic enzyme that is closely related to the pathogenesis of OP. Evidence shows that serum MMP-9 concentration is negatively correlated with bone mineral density, which is considered a biochemical marker of bone resorption and reconstruction, and an important marker for early diagnosis of OP 40 , 41 . Additionally, Guoju Hong et al showed that Robinin may inhibit osteoclast proliferation to prevent OP by down-regulating the expression of the osteoclast target gene, MMP9 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicines comprising herbal formulas are an interesting alternative to prevent osteoporosis because of their effective bone protecting properties and the lower reported side effects compared with synthetic drugs. Zhuanggu Guanjie pill is a traditional Chinese medicine formula consisting of 12 herbs including rhizoma drynariae, radix dipsaci, rhizoma cibotii and fructus psoraleae, which have beneficial effects in osteoporosis patients [ 86 ]. BHH10, a traditional Korean herbal medicine including three herbs (A. membranaceus, C. cassia, and P. amurense), has also proved effective and safe [ 87 ].…”
Section: Small Molecules Nanoparticles and Natural Productsmentioning
confidence: 99%